Analysis of innovative technologies in industry: the blockchain and the internet of things - P. A. Drogovoz; M. V. Koshkin (Вестник университета)
The rapid development of modern information technologies introduces significant changes in the work of all spheres of activity, especially in industry. The technologies, using in industry have been analyzed in the article. The prospects for the development of the blockchain technology and the industrial Internet were considered and possible problems for their implementation and development have been highlighted, such as: high cost, unemployment, long distances and long transit times, cold climate, insuffi quality of cartographic services.